2011
DOI: 10.1530/rep-10-0230
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin increases ciliary beat frequency and decreases muscular contraction in the rat oviduct

Abstract: Our laboratory previously showed that oviduct produced the greatest amount of adrenomedullin (ADM) in the rat female reproductive tract. The aim of this study is to investigate the changes in ADM levels resulting from the contact between the sperm and the oviduct and the possible roles of ADM in ciliary beating and oviductal contractility. Oviducts from Sprague-Dawley rats removed at pre-and post-ovulatory stages were cut open longitudinally and treated with ADM and/or receptor blockers before ciliary beat fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Sperm contact is another factor that seems to enhance the expression of ADM [52]. Stimulating effects of ADM is blocked by the calcitonin-gene-related peptide (CGRP) receptor antagonist [53]. In line with these studies, it has been suggested that plasma and tubal levels of ADM are lower in patients with tubal ectopic pregnancy compared to those with a normal pregnancy [54].…”
Section: Adrenomedullinmentioning
confidence: 98%
“…Sperm contact is another factor that seems to enhance the expression of ADM [52]. Stimulating effects of ADM is blocked by the calcitonin-gene-related peptide (CGRP) receptor antagonist [53]. In line with these studies, it has been suggested that plasma and tubal levels of ADM are lower in patients with tubal ectopic pregnancy compared to those with a normal pregnancy [54].…”
Section: Adrenomedullinmentioning
confidence: 98%
“…Moreover, in the oviductal secretory cells, E 2 induces the production of cAMP, which promotes adrenomedullin activation (Liao et al 2013). In rats, adrenomedullin increases CBF by acting through the calcitonin-gene-related peptide (CGRP) receptor in the oviductal epithelial cells (Liao et al 2011). …”
Section: Ciliary Beatingmentioning
confidence: 99%
“…26 It is possible that this Adm 1/2 implantation phenotype is due in part to changes in ciliary beat frequency in the oviduct. 30,31 Embryos of Adm 1/2 dams are also more likely to die or demonstrate abnormalities symptomatic of poor placental perfusion during the development of the placenta between e9.5 and e12.5. 26 Furthermore, pathological placental morphologies observed in embryos developing within Adm 1/2 uteri exhibit aberrant invasion of Adm-expressing TGCs into the decidua.…”
Section: Maternal-derived Am Is Necessary For Successful Implantationmentioning
confidence: 99%